Ivo Alexandre: an artist over time in contemporary art (Revista Apotheke, 2024)
Interview with Portuguese artist Ivo Alexandre, in 2023. Ivo Alexandre works mainly with painting, having also worked in the field of special effects for cinema.
Keywords: Ivo Alexandre; painting; mystique; Apotheke International